Case Study: Why did the Central ‎Bank of Jordan put Policies for ‎Financial Inclusion in Place?‎ - Halasa, Mona G. (Tufts Archival Research Center, 2018)
Submitted in partial fulfillment of the degree Master of Arts at the Fletcher School of Law and Diplomacy. Abstract: This capstone, case study, explores the ideas and rationale behind the decisions made by the ‎Central Bank of the Hashemite Kingdom of Jordan to incorporate policy structures for financial ‎inclusion, i.e. to include the poor population and refugees in Jordan to use financial services.